Transglutaminase 2 interactions with extracellular matrix proteins as probed with celiac disease autoantibodies. (13th April 2015) - Cardoso, Inês; Stamnaes, Jorunn; Andersen, Jan Terje; Melino, Gerry; Iversen, Rasmus; Sollid, Ludvig M.
<x xml:space="preserve">Abstract</x> Transglutaminases have been implicated in various human diseases. A prominent example is the involvement of transglutaminase 2 (TG2) in the gluten‐sensitive enteropathy celiac disease, where the enzyme is both the target of autoantibodies and responsible for the generation of immunogenic gluten epitopes. Here, we aimed to characterize the microenvironment of TG2 in the extracellular matrix (ECM) in order to gain insights into the antigenic structures that are recognized by autoantibodies in celiac disease. A panel of TG2‐specific mAbs established from gut plasma cells of celiac disease patients was employed as probes to characterize the interactions between TG2 and ECM constituents. With immunofluorescence staining, microplate protein‐binding and surface plasmon resonance assays, we found that the main epitope (epitope 1) recognized by TG2‐specific gut plasma cells overlaps with the fibronectin (FN)‐binding site of TG2. Furthermore, we found that the same TG2 amino acids that are involved in binding of epitope 1 mAbs are also important for efficient binding of FN. Notably, epitope 1 mAbs recognize TG2 in tissue sections, suggesting that some TG2 in the extracellular matrix has interaction partners in addition to FN. We demonstrate that collagen VI is a strong candidate, on the basis of its tissue expression pattern and ability to bind TG2. Collagen VI may thus serve as a matrix for deposition of TG2 in a context that can also be recognized by epitope 1‐targeting autoantibodies.